The Relationship Between Family Support And Rehospitality in Heart Failure Patients in Kemuning Room, Jombang Hospital - Subianto, Agus; Kurdi, Fahruddin; Khoiri, Ahmad Nur (Al-Hijrah Indonesia, 2023)
Congestive heart failure is a clinical problem that occurs in patients who have abnormalities, either hereditary or acquired in the structure and function of the heart, causing the development of a series of clinical symptoms of weakness and tightness as well as clinical signs of edema and crackles which result in hospitalization, poor quality of life, and shortened life expectancy. This study aims to determine the relationship between family support and re-hospitalization incidence in heart failure patients in the Kemuning room at Jombang Hospital. The research design used in this study is cross-sectional analytic. The population in this study were all heart failure patients in the Kemuning Room of the Jombang Hospital, with a total of 37 people. A sample of 33 respondents. The sampling technique used is purposive sampling. The research variable is family support and the dependent variable is the incidence of re-hospitalization in heart failure patients. which were analyzed using chi-square with α = 0.05. The results of this study indicated that the majority (60.6%) of respondents had good family support, numbering 20 people, and the majority (69.7%) of respondents who were re-hospitalized in patients with heart failure were up to six months, totaling 23 people. The analysis results obtained 0.000 <0.005, meaning there is a relationship between family support and the incidence of re-hospitalization in heart failure patients in the Kemuning room at Jombang Hospital. From this research, it is hoped that nurses can maximize the role of the family as one of the support systems in caring for congestive heart failure patients undergoing re-hospitalization.